2023
DOI: 10.1136/rmdopen-2022-002663
|View full text |Cite
|
Sign up to set email alerts
|

Work participation in patients with axial spondyloarthritis: high prevalence of negative workplace experiences and long-term work impairment

Abstract: IntroductionAxial spondyloarthritis (axSpA) is a chronic inflammatory disease that typically affects people in their second and third decades of life, which are important years for establishing a professional career. We aim to study outcomes of work participation (WP) and their associations with demographic and clinical confounders, in addition to prevalence of negative workplace experiences in axSpA.MethodsIn total, 770 patients with axSpA participated in the multicentre, observational ATTENTUS–axSpA survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Notably, this was not improved with biological treatment. 32 However, this lack of improvement is not the case in all studies, with one systematic literature review finding overall work productivity to be improved to a greater extent for axSpA patients who received biological treatment than placebo. 33 In addition, a cross-sectional questionnaire of patients with axSpA and psoriatic arthritis found that, despite biologic treatment, a high proportion of patients had abnormal sleep behaviour which was associated with impaired HRQoL and a higher rate of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, this was not improved with biological treatment. 32 However, this lack of improvement is not the case in all studies, with one systematic literature review finding overall work productivity to be improved to a greater extent for axSpA patients who received biological treatment than placebo. 33 In addition, a cross-sectional questionnaire of patients with axSpA and psoriatic arthritis found that, despite biologic treatment, a high proportion of patients had abnormal sleep behaviour which was associated with impaired HRQoL and a higher rate of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this was not improved with biological treatment. 32 However, this lack of improvement is not the case in all studies, with one systematic literature review finding overall work productivity to be improved to a greater extent for axSpA patients who received biological treatment than placebo. 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with active spondyloarthritis have high rates of general hospitalization for various reasons, including emergency room visits, outpatient visits, and investigations [11]. Patients with psoriatic arthritis have more frequent and longer periods of temporary disability compared to their peers [12]; up to 74.1% of patients with active axial spondyloarthritis face employment problems [13], and almost a quarter (23.4%) are unable to work fully due to illness [14]. Persistent disability, according to various sources, occurs in 13-45% of patients with axial spondyloarthritis [4], and in 16-39% in psoriatic arthritis patients [15].…”
Section: Introductionmentioning
confidence: 99%